2019
DOI: 10.1177/1747493019858780
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin for primary prevention of stroke in individuals without cardiovascular disease—A meta-analysis

Abstract: Background The benefits of aspirin for primary prevention of stroke are uncertain. Methods We performed a cumulative meta-analysis of trials investigating aspirin for primary prevention of cardiovascular disease with a focus on stroke. We assessed the effects of aspirin on non-fatal stroke, hemorrhagic stroke, non-fatal myocardial infarction, all-cause mortality, cardiovascular mortality, major gastrointestinal bleeding, and an analysis of net clinical effect, in populations without a history of clinical or su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
2
20
0
1
Order By: Relevance
“…Generally speaking, the risk of hemorrhagic stroke is well acknowledged to increase in patients taking aspirin. Therefore, it is plausible that aspirin could reduce the risk of ischemic stroke recurrence while it could cause significantly more fatal hemorrhagic stroke 37 , 38 compared with nicametate. However, as time to recurrence has been also included in the survival time from the date if first-time stroke, through recurrence, and then to death from cerebrovascular disease, it is not good not to take time to recurrence into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, the risk of hemorrhagic stroke is well acknowledged to increase in patients taking aspirin. Therefore, it is plausible that aspirin could reduce the risk of ischemic stroke recurrence while it could cause significantly more fatal hemorrhagic stroke 37 , 38 compared with nicametate. However, as time to recurrence has been also included in the survival time from the date if first-time stroke, through recurrence, and then to death from cerebrovascular disease, it is not good not to take time to recurrence into account.…”
Section: Discussionmentioning
confidence: 99%
“…Third, according to the mechanism and evidence-based researches, the treatment with aspirin for prevention on primary or secondary stroke may increase the risk of hemorrhagic stroke 37 , 38 . However, the cause of death ascertained by Health and Welfare Data Science Center (HWDC), in light of the regulation for open data use, only 26 and 36 brief classifications of cause of death were provided for before 2007 and 2008 onward, respectively (see Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although preventive medication was not the aim of our study, it is worth mentioning that while one could suggest routine use of antiplatelet medication in certain patients with white matter hyperintensities on MRI and co-existing risk factors, the current evidence does not support using antiplatelets as a primary prevention for stroke. 23,24…”
Section: Clinical Implications Of Incidental White Matter Hyperintensitiesmentioning
confidence: 99%
“…4 In the nearly 30 years since the Physicians Health Study was reported, it has become very clear that doses of aspirin even as low as 81 mg (a single baby aspirin tablet) per day could cause significant gastrointestinal bleeding. [5][6][7][8][9][10][11][12][13][14] The risk of gastrointestinal bleeding with aspirin is much higher in individuals 65 years and older 5,13 (Table 1). Saad et al 5 estimated that the risk of major bleeding nearly doubled with each decade of age even without the use of aspirin.…”
mentioning
confidence: 99%